Emotional Intelligence: perspectives and reflections before the era of the new normality - Ramírez Molina, Reynier Israel; Pinzón Acosta, Manuela Valentina; Ramírez Molina, Ramineth Joselin; Antequera Amaris, Ricardo Romario; Lay Raby, Nelson David; Nieto Medina, Paula (Opción)
The research analyzes emotional intelligence in the era of the new normal. From the dialogic hermeneutics, conception of classical and current disciplinary theoretical referents, giving rise to perspectives and reflections. It is concluded that the strategies for emotional regulation, social awareness and facilitating emotions are articulated to integrate emotional intelligence, impacted by economic, social, environmental and political factors, insisting on the reinvention of the living being, modifying structures, models and management of people in business, allowing selfrecognition of the human being and the assessment of their behavior, highlighting their sensitivity and control